Modeling the inactivation of Bacillus subtilis spores by ethylene oxide processing - Mendes, G. C. (2012)
Ethylene oxide is currently a dominant agent in medical device sterilization. This work intends to study the main effects and interactions of temperature, ethylene oxide concentration, and relative humidity on commercial spore strips of Bacillus subtilis, var. niger (ATCC 9372) inactivation, the most common microorganism used in controlling the efficacy of the process. Experiments were carried out using a full factorial experimental design at two levels (2(3) factorial design). Limit target exposure conditions for ethylene oxide concentration, temperature, and relative humidity were 250-1,000 mg EO/l, 40-60A degrees C, and 50-90%, respectively. Adopting a different approach from the first-order kinetics, a Gompertz model was successfully applied in data fitting of the inactivation curves. Bacillus subtilis kinetic behavior presented a sigmoidal inactivation with an initial shoulder (lambda), followed by a maximum inactivation rate (k(max)), these being model parameters. It was concluded that temperature and ethylene oxide concentration were the most significant factors and consequently, additional experiments were carried out aiming at describing the parameters' dependence on these process factors. Mathematical relations describing such dependences were successfully developed and included in the Gompertz kinetic model. The predictive ability of this integrated model was assessed, and its adequacy in predicting B. subtilis inactivation was proven.